Conventional imaging techniques plus 18F-Fluorocholine PET/CT: a comparative study of diagnostic accuracy in localizing parathyroid adenomas in primary hyperparathyroidism - Chiu, Wei-Yih; Chen, Kuen-Yuan; Shun, Chia-Tung; Wu, Ming-Hsun; Tsai, Keh-Sung; Chiu, Ching-Hung; Yang, Wei-Shiung; Yen, Ruoh-Fang (Frontiers in Endocrinology, 2025)
BackgroundCurrently 18F-Fluorocholine (FCH)-PET/CT is a choice beyond widely used techniques like ultrasound (US) and technetium-99m sestamibi (MIBI) for primary hyperparathyroidism (pHPT). It remains uncertain how FCH-PET/CT collaborates with those two traditional modalities. This study aims to prospectively evaluate the effectiveness of individual, complementary, and combined utilization of FCH-PET/CT for preoperative localization.MethodsAll participants underwent US, MIBI, and FCH-PET/CT examinations, and eligible patients underwent parathyroid surgery based on surgical indications and patient preferences. McNemar’s test compared diagnostic performance between imaging techniques and Spearman’s rank correlation correlated FCH-PET/CT parameters with lesion volume, laboratory, and histological features.Results63 out of 83 recruited patients underwent parathyroidectomy. Histologically confirmed parathyroid lesions were found in 69 glands among 63 patients. FCH-PET/CT exhibited higher sensitivity than US, MIBI, and US/MIBI combination (87.0% vs. 49.3%, P <0.001; vs. 49.3%, P <0.001; vs. 66.7%, P=0.006). As a second-line modality after US, MIBI, and US/MIBI combination, FCH-PET/CT achieved sensitivities of 88.6%, 77.1%, and 80.9% in detecting US-negative lesions, MIBI-negative lesions, and lesions with negative or conflicting US/MIBI results, respectively. Among various imaging combinations, the combined use of US and FCH-PET/CT showed significantly higher sensitivity than FCH-PET/CT alone (94.2% vs. 87.0%, P=0.025) and similar sensitivity with higher specificity than the combination of all three modalities (sensitivity: 94.2% vs. 95.7%, P=0.317; specificity: 98.9% vs. 95.1%, P=0.008).ConclusionsFCH-PET/CT is effective as a first-line or complementary technique, irrespective of prior US, MIBI or US/MIBI combination. US combined with FCH-PET/CT appears to be the most effective localization strategy among the modalities evaluated in this study. Our findings support an ultrasound-first approach for localizing primary hyperparathyroidism, with FCH-PET/CT referral in uncertain cases to enhance success rates.